2021
DOI: 10.20944/preprints202107.0553.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Cytological Model for the Identification of Early Oral Cancer Diagnostic Markers: The Carcinoma Sequence Model

Abstract: Most oral squamous cell carcinomas (OSCCs) arise from oral epithelial dysplasia; however, there is no useful marker for early OSCC detection, likely owing to the inability to continuously observe the carcinoma sequence. We aimed to establish an experimental model to observe changes in the sequential expression pattern of mRNA and protein in the same rat using liquid-based cytology techniques. Cytology specimens were collected from a 4-nitroquinoline 1-oxide-induced rat tongue cancer model at 2, 5, 8, 11, 14, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…In a previous study, we established a novel experimental animal model that allowed our research group to observe the carcinoma sequence of OSCC and reported that Brd4 and c-Myc could be useful biomarkers for the early detection of oral cytology (9). Moreover, several prospective biomarkers have been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we established a novel experimental animal model that allowed our research group to observe the carcinoma sequence of OSCC and reported that Brd4 and c-Myc could be useful biomarkers for the early detection of oral cytology (9). Moreover, several prospective biomarkers have been reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Oral cytology is a simple, non-invasive, and relatively reliable OSCC screening method performed since 1951 and has been improved using state-of-the-art instruments and updated diagnostic criteria (7). In particular, the liquid-based cytology (LBC) technique can detect morphological changes as well as DNA, RNA, and protein expression changes in the same samples (8,9). Moreover, LBC samples have been reported to have lower inadequate rates and higher sensitivity and specificity than conventional cytology (CC) in the cervical and oral regions (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%